Impact of Climate Change on Water Resources in Kashmir, India (International Journal of Innovative Research in Computer Science & Technology, 2022)
The main objective of the study was to  test the performance and feasibility of SWAT model for  prediction of stream flow in state of Jammu and Kashmir  in India. The model was auto calibrated for a period of 8  years (2013 – 2021) using Swat Cup software. The SuFi2  algorithm in Swat Cup was adopted for auto calibration of  the model. The calibrated model was validated for the  three gauging stations for a period of 8 years (2013 – 2021). The land use map used for the calibration period  was for the year 2013 and that for the validation period  was for the year 2013. The simulated monthly stream low  has Nash Sutcliffe efficiency value of 0.60, 0.69 and 0.71  for the calibration period for the said area respectively.  The model results in good performance showing that it is  feasible for predicting stream flow in under changing land  use and climate conditions.
Keywords: Climate Change; Economic Pathways; Precipitation; Swat Modelling; Temperature